Structural analysis of technical-tactical activities in table tennis - Munivrana, G. (Croatian Sports Medicine Journal, 2020)
For the purpose of determining the hierarchical structure of technical-tactical activities in table tennis 110 technical-tactical elements, best representing the entire group of technical-tactical skills used in table tennis, were selected and a new measuring instrument (a questionnaire) was formulated that takes advantage of the expert knowledge of top, world class table tennis coaches. As the experts evaluated the importance and role of technicaltactical elements in table tennis the results have showed that the overall structure of the technical-tactical activities forming the table tennis technique can be divided into three basic groups; a group of technical-tactical elements (A) used in the phase of preparing one`s own and disabling the opponent`s attack; a group of technical-tactical elements (B) used in the phase of attack and counterattack; and a group of technical-tactical elements (C) used in the phase of defense. Within the each of the basic groups, subgroups with even more homogeneous mutual characteristics have been identified, what enable even more precise determination of the role and hierarchical importance of each individual group/subgroup of technical-tactical elements in different segments of the table tennis game.